The influence of marketing tools on consumer behavior and its assessment - Kovanovienė, Viktorija; Mačytė, Raminta; Petkevičiūtė, Rasa; Zaikauskaitė, Greta (Vilnius University Open Series, 2019)
The article aims to analyse and evaluate the influence of marketing tools on consumer behavior. In order to investigate the topic, a thorough analysis of scientific literature was performed and followed by systematization and generalization of different theories and academic sources. The research revealed that the use of various marketing tools such as advertising and online communication through social media or blogs allows to gain exposure for businesses and have a positive impact on consumer behavior. On the other hand, it is important to note that both micro and macro environment have to be taken into account, as individuals might make different decisions based on the surrounding cultural, social and market contexts. Based on the proposed theoretical model of the influence of marketing tools on consumer behavior, there is a positive correlation between sociological variables, external stimuli and marketing communications. The holistic model should be empirically validated and revised once investigated in practice.
Keywords: the influence of marketing tools, marketing communications; consumer behavior; consumer decision-making process; consumer behavior assessment